Influence of aging on transformation characteristic and phase structure of a Cu-12.4Al-1.2Ti-1.2Ta shape memory alloy - Yildiz, Koksal (Springer Heidelberg, 2020)
The effect of aging on the properties of a Cu-12.4Al-1.2Ti-1.2Ta (wt.%) high-temperature SMA was investigated throughout SEM/EDS, XRD and DSC experiments. It was found that the transformation behavior, the thermal properties and the phase structure of the alloy remarkably changed with homogenization process performed at 900 degrees C for 20 min and then aging at 400 and 500 degrees C for 1 h. Structural and morphological investigations revealed that the homogenization process caused martensitic decomposition in the alloy and austenite phase domains remained. Afterward, with the effect of thermal aging, the amount of the austenite phase increased and the alpha-phase domains nucleated and grew in the alloy. At elevated aging temperature, the amounts of the austenite and the alpha-phases in the alloy considerably increased and martensitic morphology disappeared. As a result of these, the phase structure of the alloy affected its thermal behavior and led to exhibit irreversible one-stage martensitic transformation behavior.
Keywords: Shape memory materials; Martensite; Degradation; Phase structure